Virtue Ethics and Ubuntu in Leadership towards the Promotion of Ethical Organisational Operations - Angelo Nicolaides; Nkosinathi Dludla (Athens Journal of Business & Economics, 2023)
The objective of the conceptual literature study is to assess virtue ethics as a viable ethical leadership theory in African countries, more explicitly South Africa. We pinpoint some deficits in ethical leadership, which could be addressed through adopting a virtue ethics driven ethical organisational climate in order to positively enhance business practices and service to the community and society in general. This paper supports the notion of virtue ethics as being the suitable one for the purpose of motivating an ethical climate which leads to sustainable business. Leaders need to assume core responsibility for promoting ethics and should reinforce the notion of morally correct behaviour at all times through their demonstrable ethical conduct. This necessitates that leaders’ must exhibit virtue and possess particular qualities and know how to apply these to workplace situations. Virtue ethics as one of numerous ethical theories, certainly has a role to play in the contemporary discourse in which corruption is rife. In addition, it aligns in many ways with the notion of Ubuntu. We argue that ethical leadership behaviour based on virtue and an Ubuntu spirit, is critical in supporting an ethical climate in any organisation and it promotes sustainability. The study employed an interpretivistic expository methodology of textual analysis based on extant literature. Thus, it is to an extent hermeneutic in nature and leads to insights supporting the notion of using Virtue ethics and Ubuntu to inform practice in African organisations and society.